YIELD RESPONSES OF WATERMELON (CITRULLUS LUNATUS (THUMB) IN A COASTAL PLAIN SOIL UNDER VARIABLE FERTILIZER RATES AND IRRIGATION REGIME IN A DRY SEASON PRODUCTION CYCLE - EGBUCHUA, Collins; ENUJEKE, Emmanuel Chukudinife (International Journal of Research -GRANTHAALAYAH, 2021)
Field experiments were conducted during 2017 and 2018 cropping seasons at Illah, Delta North ecological zone of Nigeria to investigate the appropriate rates of NPK fertilizer and irrigation intervals in relation to yield response of water melon (Citrullus lunatus). The site had sandy loam texture, low in organic carbon (0.38%), low in total nitrogen (0.064%), available phosphorus (6.83 mgkg-1) and cation exchange capacity (6.74 cmolkg-1). The fertilizer rates were (0:0:0), (50:25:25), (80:40:40), and (120:60:60) KgN, P2O5 and K2O/ha and irrigation regimes of 6:12:18 days. It was a factorial experiment laid out in a Randomized Complete Block Design with three replicates. Results indicated that increase in fertilizer rates from 0:0:0 to 80:40:40 kg/ha significantly increased growth and fruit yield. Further increase to 120:60:60 kg/ha depressed yield. Increase irrigation intervals from 6 -12 days also influenced significantly growth and fruit yield and further increase to 18 days intervals affected negatively the parameters. Interaction effects between fertilizer x irrigation intervals were not significant. Correlation analysis showed that the growth and yield characters were significant and positively correlated with fruit yield. Results indicated that fertilizer rates and 12 days irrigation interval were adequate and recommended for increased production of watermelon in the study area.